Stress Kerja pada Perawat Rumah Sakit Pusat Otak Nasional Prof. Dr. dr. Mahar Mardjono - Mustakim Mustakim; Eka Luthfi Nur Andini; Intan Rosenanda Sofiany (Universitas Muhammadiyah Semarang, 2022)
Background: Nurses are one of the professions with a high level of work stress. The 2018 Indonesian National Nurses Association survey showed 50.9% of nurses in Indonesia experienced work stress. Objective: This study aims to determine the factors associated with work stress on nurses at the inpatient installation of the Jakarta National Brain Center Hospital in 2021. Method: This study is a quantitative correlational study with a cross-sectional design. The population in this study were all nurses in the inpatient installation of the National Brain Center Hospital. Sampling was done by non-probability sampling with accidental sampling technique and obtained 56 respondents. Result: As many as 39.3% of respondents who experience work stress in the severe category. The results of bivariate analysis showed that there was a significant relationship between age (P=0.036), marital status (P=0.017), physical environment (P=0.023) and social support (P=0.004) with the incidence of work stress. However, there was no significant relationship between gender (P=0.132), tenure (P=0.458), interpersonal conflict (P=0.631), workload (P=0.968), shift work (P=0.072) and activities outside of work. (P=0.068) on work stress. Conclusion: Agencies should provide workloads that are in accordance with the abilities and competencies of workers while still paying attention to workers' rights in order to prevent work stress on nurses.